Peran Konteks dalam Penentuan Makna Tersirat Teks: Kasus Tiga Teks Forensik Bahasa Indonesia - Pastika, I Wayan (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 1 (2021), 2021)
Freedom of expression in Indonesia has reached the best momentum after the reformation era for democracy develops very successfully to the right direction in the last two decades. One such freedoms is free media and this progressive opportunity often been manipulated by particular users. Thanks to the Indonesian government that has issued constitutional law to punish wrong doing of irresponsible users on electronic transation of information i.e UU ITE Number 11 year 2018 and UU ITE Number 19 year 2016. In this paper there are two research questions to investigate: (1) What linguistics strategy is applied to determine implied meaning of a text; (2) How socio-pragmatic contexts and intertexts play a significant role in analyzing the message. The objective of the research is to formulate a Forensic Linguistics perspective on determining implied meaning and message. The result is that implied meaning must be searched by employing lexico-grammatical structures and supported by socio-pragmatic contexts, namely, deictic, implicature and speech acts. It is concluded that in investigating forensic texts particularly to find out deep structure of meaning and messages behind the surface text, microlinguistics and macrolinguistics properties should be imposed in order to formulate language crime supported by linguistic evidences.